Estimating Population Mean in Sample Surveys - Dr. Vyas Dubey; Dr. Minal Uprety; Ujjwal Dubey (International Journal of Engineering and Management Research, 2020)
The paper deals with a generalized estimator of population mean which includes several estimators as its particular cases. Under certain conditions, the proposed estimator is more efficient than existing estimators. Results are supported by numerical illustration.